The first proandric species of Tritogenia Kinberg, 1867 from Botswana, Tritogenia talana sp.n. (Clitellata, Crassiclitellata, Tritogeniidae) - Nxele, Thembeka Clara; Plisko, Jadwiga Danuta; Ramongalo, Boipelo K. (Zootaxa, 2018)
The earthworm fauna of Botswana is hitherto unknown. A first collecting trip to the regions of Chobe and Tuli Block resulted in the discovery of a new species, Tritogenia talana sp.n. Its reproductive organs show some level of degeneration when compared to other species of Tritogenia. The spermathecae were not observed, testes and sperm funnels are in proandric condition and seminal vesicles are absent. This is the first record of an earthworm species from Botswana.